"Un hombre sin barbas": the Transgender Protagonist of La Monja Alférez (1626). (2nd April 2016) - Allan, Madera Gabriela
ABSTRACT: Catalina de Erauso was born in San Sebastián at the end of the sixteenth century. When she was four years old, her parents placed her in El Antiguo convent, from which she escaped a decade later. Once free, she cut off her hair, dressed as a page and traveled throughout the Peninsula for four years before embarking for the Indies, where she worked as a merchant, soldier and muleteer for nearly two decades without being outed. Fighting under an assumed name in Chile, Erauso rose to the rank of second lieutenant. In 1617, after killing a man over a card game, Erauso confessed that she was a woman and a virgin to avoid execution. She thus became an instant and enduring celebrity, known by the somewhat misleading epithet "Lieutenant Nun, " whose story circulated in letters, petitions, relaciones, a memoir and a comedia . Most accounts of Erauso's adventures titillate audiences by recounting gender bending "grandes hazañas", but ultimately affirm her anatomic femininity. In stark contrast, Juan Pérez de Montalbán's play La Monja Alférez (1626) depicts a trans man known by his enlisted name, Alonso de Guzmán. While the relationship between the play's plot and Erauso's life is somewhat tenuous, the protagonist shares certain essential characteristics with the historical personage, including martial and erotic virtuosity. In this article, I argue that Pérez de Montalbán's protagonist moves beyond the coherent, but precarious, masculine identity produced by his performative violence and seductions by emulating classical heroes, suffering a temporary inversion to emerge as an exemplary man and a giver of women.